A new species of Platydecticus (Orthoptera: Tettigoniidae) from the Coastal Atacama Desert in Chile - Vera Sánchez, Alejandro; Zúñiga-Reinoso, Álvaro (Zootaxa, 2026)
Platydecticus pasaptur sp. nov. is described based on both males and females. The species is easily distinguishable by the following combination of characters: narrow and sulcate fastigium; in males, the subgenital plate unmodified, broad pseudocercus, short cerci and titillator median lobe digitiform, sulcate, and covered with black spines. COI gene of one specimen is included as genotype of the species. The peculiar habitat and distribution of this small species is discussed as one of the northernmost distribution within the genus.